Manuscript Qur'ans in Libya An Inductive Descriptive Study (Journal of Human Sciences, 2024)
This research is concerned with collecting information about the Libyan Qur’an. This research came in an introduction, four sections, and a conclusion. The introduction included the importance of the study, the problem of the research and previous studies, the research methodology, and its objectives. As for the introduction, it contains an introduction to the Libyan country and the importance of the manuscripts of the Qur’an. As for the first section, it contains extrapolation. of the manuscripts of the Qur’ans in the Libyan Jihad Center. The second section includes an investigation of the manuscripts of the Qur’ans at the University of Benghazi. The second section contains an investigation of the manuscripts of the Qur’ans in the Igdams Center and private libraries. The fourth section includes a study of examples of the manuscripts of the Qur’ans. This investigation is taken from the manuscript indexes. The research concluded with a conclusion containing results. The research is: that the Qur’ans at the University of Benghazi are the most, then the Libyan Jihad Center, then the Igdams Center, then the Qur’ans that are in people’s hands, and that the use of colors in ducks is apparent in all the Qur’ans, and the Qur’ans came in a variety of designs and settings, and it is possible through a study of the Qur’ans to determine Several problems in drawing Adjustment and more